Electrochemical device and electronic apparatus
By improving the electrolyte formula and the physical parameters of the synergistic positive electrode finishing tape, it meets the specific relationship, and solves the problem of wrinkling failure in high-temperature storage, realizing the battery appearance and high ionic conductivity of the electrolyte.
Patent Information
- Application Number
- CN202411989802.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-30
AI Technical Summary
PET positive electrode tailing tape is prone to wrinkle failure during high-temperature storage, resulting in battery deformation and poor appearance. The existing improvement solutions are costly and do not have high adaptability to commercial electrolytes.
By improving the formulation of the electrolyte and synergistic physical parameters of the positive electrode finishing tape, the impact of electrolyte by-products on the positive electrode finishing tape is suppressed, and the relationship between specific organic solvents, electrolyte additives and positive electrode finishing tape is met to prevent the wrinkling failure of the positive electrode finishing tape in high-temperature storage.
Effectively suppress the failure of the positive electrode tailing tape in high-temperature storage, maintain the good appearance of the battery, and ensure that the electrolyte has a high ionic conductivity.
Smart Images

Figure CN119742423A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to electrochemical devices and electronic devices. Background Art
[0002] The positive electrode tape of lithium-ion batteries is one of the important components of the battery. The positive electrode tape can effectively improve the safety of the battery by covering the end of the positive electrode to prevent the burrs of the electrode from piercing the diaphragm and causing a short circuit between the aluminum foil and the negative electrode. PET tape is a commonly used positive electrode tape, but long-term high-temperature storage of the battery will cause the PET positive electrode tape soaked in the electrolyte to wrinkle and fail, resulting in deformation of the battery and poor appearance.
[0003] In the related art, the wrinkling and failure of the PET positive electrode tailing tape during high-temperature storage is generally prevented by improving the electrolyte resistance of the PET positive electrode tailing tape itself.
[0004] However, the improvement cost of the above solution is high and its compatibility with commercial electrolytes is not high enough. Summary of the invention
[0005] In order to solve or partially solve the problems existing in the related art, the present application provides an electrochemical device and an electronic device, which can inhibit the influence of electrolyte by-products on the positive electrode finishing tape by improving the formulation of the electrolyte and coordinating the physical parameters of the positive electrode finishing tape, thereby preventing the positive electrode finishing tape from wrinkling and failing during high-temperature storage, and maintaining the good appearance of the battery.
[0006] The first aspect of the present application provides an electrochemical device, comprising a housing, a battery cell disposed in the housing, and an electrolyte injected into the housing, wherein the electrolyte comprises a lithium salt, an organic solvent and an electrolyte additive, wherein the organic solvent comprises a chain ester solvent, and the electrolyte additive comprises a fluorine-containing compound and a boron-containing compound; the battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises a positive electrode current collector, wherein one side surface of the positive electrode current collector comprises a blank area and a filler area, wherein the filler area is coated with a positive electrode active material layer, and a positive electrode tailing tape is pasted between the blank area and the filler area, and the positive electrode tailing tape faces the separator;
[0007] The organic solvent, the electrolyte additive and the positive electrode finishing tape satisfy the following relationship:
[0008] 1≤A / (C+D)×B+100 / E≤4
[0009] In the formula, the mass percentage of the chain ester solvent to the organic solvent is A%, and the pasting area of the positive electrode tailing tape is B dm 2, C is the mass percentage of the fluorine-containing compound in the electrolyte is C%, the mass percentage of the boron-containing compound in the electrolyte is D%, and before injecting the electrolyte, the total moisture content of the separator and the negative electrode sheet in the battery cell is E ppm.
[0010] As an optional embodiment, the fluorine-containing compound includes at least one of the following compounds:
[0011]
[0012]
[0013] As an optional embodiment, the structural formula of the boron-containing compound is as follows:
[0014]
[0015] In structural formula 2, R1, R2 and R3 are each independently selected from at least one of a H atom, a C1-C10 alkyl group, a C6-C20 aryl group and a cyano group.
[0016] As an optional embodiment, the boron-containing compound includes at least one of the following compounds:
[0017]
[0018]
[0019] As an optional embodiment, the chain ester solvent includes at least one of diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethyl propionate, propyl propionate, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, methyl butyrate, ethyl butyrate, methyl acrylate, and ethyl acrylate; preferably, the chain ester solvent contains at least propyl propionate; and / or, the organic solvent also includes a cyclic ester solvent, and the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, and cyclopentane sulfone.
[0020] As an optional embodiment, the mass percentage of the organic solvent in the electrolyte is 20% to 80%.
[0021] As an optional embodiment, A is 20-80; and / or B is 0.02-0.5; and / or C is 1-25; and / or D is 0.1-5; and / or E<120.
[0022] As an optional embodiment, A is 40-80; C is 5-25; and / or D is 0.1-3.
[0023] As an optional embodiment, one end of the positive electrode tailing tape is pasted in the filler area, and the other end is pasted in the blank area, and the area S of the positive electrode tailing tape pasted in the blank area is K Greater than the area S pasted in the filler area T .
[0024] As an optional embodiment, 1.5S T ≤S K ≤2S T .
[0025] A second aspect of the present application provides an electronic device, comprising the electrochemical device described above.
[0026] The technical solution provided by this application may have the following beneficial effects:
[0027] Since the degradation of the positive electrode finishing tape during (after) high-temperature storage is related to whether some chain ester solvents (such as DMC) produce by-products, and whether some chain ester solvents produce by-products is related to the stability of the SEI film and the trace moisture content in the electrolyte, the stability of the SEI film is further related to the content of fluorine-containing compounds and boron-containing compounds, and the trace moisture content in the electrolyte is related to the total moisture content of the separator and the negative electrode sheet in the battery cell before injection (since the positive electrode sheet uses an organic solvent, the water content can be ignored, and the water solvent used in the negative electrode sheet and the separator mainly determines the water content in the battery cell before injection, so the water content of the battery cell before injection is mainly related to the total moisture content of the separator and the negative electrode sheet), therefore, controlling the content of fluorine-containing compounds and boron-containing compounds can maintain the stability of the SEI film; and controlling the total moisture content of the separator and the negative electrode sheet in the battery cell before injection can reduce the trace moisture in the electrolyte. The content of fluorine-containing compounds and boron-containing compounds needs to be compatible with the content of chain ester solvents and the pasting area of the positive electrode tailing tape. This is because when the content of chain ester solvents is high and the content of fluorine-containing compounds and boron-containing compounds is relatively low, it will not be able to effectively improve the stability of the SEI film, causing the chain ester solvent to undergo an electrochemical reaction at the negative electrode to generate lithium methanol; when the content of chain ester solvents is low and the content of fluorine-containing compounds and boron-containing compounds is relatively high, it will cause the electrolyte viscosity to increase, the film formation impedance to increase, the lithium ion conduction efficiency to decrease, and the battery's kinetic performance to deteriorate. In addition, when the pasting area of the positive electrode tailing tape is large, the battery capacity will decrease; and when the content of fluorine-containing compounds and boron-containing compounds is relatively high, the electrolyte viscosity will increase, and the positive electrode tailing tape will not be effectively prevented from wrinkling. When the content of chain ester solvents is low, and the pasting area of the positive electrode tailing tape is small, and the content of fluorine-containing compounds and boron-containing compounds is relatively high, the electrolyte viscosity will increase, the film formation impedance will increase, the lithium ion conduction efficiency will be reduced, and the battery's kinetic performance will be deteriorated. Therefore, the inventors have found that when the organic solvent, the electrolyte additive and the positive electrode tailing tape meet 1≤A / (C+D)×B+100 / E≤4, the content of fluorine-containing compounds and boron-containing compounds can be balanced with the content of chain ester solvents and the content of fluorine-containing compounds and boron-containing compounds can be balanced with the pasting area of the positive electrode tailing tape, and the trace moisture in the electrolyte can be controlled, thereby effectively inhibiting the failure of the positive electrode tailing tape during (after) high-temperature storage, and ensuring that the electrolyte has a high ionic conductivity.
[0028] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0030] Figure 1 It is a schematic diagram of the structure of the positive electrode sheet shown in the embodiment of the present application.
[0031] In the figure, 1, positive electrode sheet; 10, positive electrode current collector; 11, positive electrode active material layer; 12, positive electrode finishing tape; K, blank area; T, filler area; S K , the pasting area of the positive electrode tailing tape in the blank area; S T , the bonding area of the positive electrode finishing tape in the filling area. DETAILED DESCRIPTION
[0032] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0033] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0034] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0035] PET tape is a commonly used positive electrode tailing tape, but long-term high-temperature storage of the battery will cause the PET positive electrode tailing tape immersed in the electrolyte to wrinkle and fail, thereby causing the battery to deform and cause poor appearance. In the related art, the wrinkling and failure of the PET positive electrode tailing tape during high-temperature storage is generally prevented by improving the electrolyte resistance of the PET positive electrode tailing tape itself. However, the improvement cost of the above solution is high and the compatibility with commercial electrolytes is not high enough.
[0036] In response to the above problems, an embodiment of the present application provides an electrochemical device that can suppress the impact of electrolyte byproducts on the positive electrode finishing tape by improving the formulation of the electrolyte and coordinating the physical parameters of the positive electrode finishing tape, thereby preventing the positive electrode finishing tape from wrinkling and failing during high-temperature storage, and maintaining the good appearance of the battery.
[0037] See also Figure 1 As shown, an embodiment of the present application provides an electrochemical device, comprising a housing, a battery cell arranged in the housing, and an electrolyte injected into the housing, wherein the electrolyte comprises a lithium salt, an organic solvent and an electrolyte additive, wherein the organic solvent comprises a chain ester solvent, and the electrolyte additive comprises a fluorine-containing compound and a boron-containing compound; the battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet 1 comprises a positive electrode collector 10, wherein one side surface of the positive electrode collector 10 comprises a blank area K and a filler area T, wherein the filler area T is coated with a positive electrode active material layer 11, and a positive electrode tailing tape 12 is pasted between the blank area K and the filler area T, and the positive electrode tailing tape 12 faces the separator; wherein the organic solvent, the electrolyte additive and the positive electrode tailing tape satisfy the following relationship:
[0038] 1≤A / (C+D)×B+100 / E≤4
[0039] Wherein, the mass percentage of chain ester solvent in organic solvent is A%, and the pasting area of positive electrode tail tape is B dm 2 , C is the mass percentage of fluorine-containing compounds in the electrolyte, which is C%, the mass percentage of boron-containing compounds in the electrolyte is D%, and before injecting the electrolyte, the total moisture content of the separator and the negative electrode sheet in the battery cell is E ppm.
[0040] In the embodiments of the present application, the electrochemical device may be a battery such as a lithium-ion battery, and the battery housing may be used to encapsulate the battery cell and the electrolyte. The battery housing may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. It may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and as plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate, etc. may be listed. The present application has no particular restrictions on the shape of the battery, which may be cylindrical, square, or any other shape.
[0041] The battery cell of the embodiment of the present application can be formed by winding a positive electrode sheet, a negative electrode sheet and a separator. Specifically, the positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then the stacked electrode sheets and the separator are wound to obtain a battery cell, wherein from the inside to the outside are the positive electrode sheet, the separator and the negative electrode sheet. The battery cell is placed in a shell, and the battery cell is baked to remove moisture, and then an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0042] In the embodiment of the present application, the positive electrode sheet includes a positive electrode current collector, and the positive electrode current collector has two sides, namely, side a and side b, and both side a and side b have a filling area and a blank area. The filling area of side a is longer than the filling area of side b, and side a is bonded to the diaphragm when preparing the battery cell; the filling areas of side a and side b are coated with a positive electrode active material layer, and a positive electrode tailing tape is pasted between the blank area of side a and the filling area. On the one hand, the positive electrode tailing tape can provide a safe position for the tail of the positive electrode to ensure that the negative electrode pole piece at the tail of the winding core exceeds the part of the positive electrode pole piece in length and width. It can ensure that during the charging process, the negative electrode can embed lithium ions from the positive electrode, thereby avoiding the accumulation of lithium ions at the edge of the negative electrode, thereby reducing the occurrence of lithium precipitation; on the other hand, the positive electrode tailing tape can wrap the upper and lower edges of the blank area to prevent the burrs on the edge of the positive electrode empty foil from piercing the diaphragm. Among them, the positive electrode tailing tape can be made of polypropylene PP material, polyimide PI, polyethylene terephthalate PET and other materials. Polyethylene terephthalate PET material is preferred.
[0043] In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. Preferably, the positive electrode current collector is a metal material.
[0044] In the embodiment of the present application, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of lithium cobalt oxide, nickel cobalt manganese ternary material, lithium iron phosphate and lithium manganese oxide. Preferably, the positive electrode material is lithium cobalt oxide or nickel cobalt manganese ternary material.
[0045] In a specific embodiment, the positive electrode active material layer further includes a conductive agent and a binder. The conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, graphene, etc. The binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.
[0046] The embodiments of the present application have no particular restrictions on the material and shape of the diaphragm, as long as it does not significantly impair the effect of the present application. It may include materials in the form of porous sheets or non-woven fabrics with excellent liquid retention, and the materials of resin or glass fiber diaphragms include but are not limited to polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc., and can be specifically set according to needs.
[0047] In an embodiment of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material coated on at least one side of the negative electrode current collector. The negative electrode active material includes at least one of graphite, hard carbon, silicon, silicon oxide compounds, and silicon carbon compounds. Preferably, the negative electrode active material is silicon.
[0048] The present application does not limit the selection of the negative electrode current collector, which can be selected according to actual needs, such as copper foil. The negative electrode active material layer of the present application includes a negative electrode active material and a binder. The negative electrode active material includes a carbon material and a silicon material. The present application does not limit the selection of the carbon material, which can be selected according to actual needs, such as graphite, carbon black, hard carbon, soft carbon, etc.; the present application does not limit the selection of the silicon material, which can be selected according to actual needs, such as silicon oxide, pre-lithiation silicon oxide, pre-magnesiation silicon oxide material, silicon-carbon composite material, elemental silicon, etc. The binder of the present application includes polypropylene compounds and styrene-butadiene rubber. Polypropylene compounds refer to polypropylene derivatives, such as polyacrylic acid, polyacrylonitrile, polyacrylamide, polymethyl acrylate, etc.
[0049] Since dimethyl carbonate (DMC) and chain ester solvents with similar structures will undergo electrochemical reactions at the negative electrode to generate lithium methylate when the SEI film is unstable, and can also undergo hydrolysis reactions with trace amounts of water in the electrolyte to generate methanol, these two byproducts can catalyze the degradation of the positive electrode tailing tape, so the positive electrode tailing tape immersed in the electrolyte during (after) high-temperature storage is prone to lose viscosity and wrinkle and fail, causing the battery to deform. The embodiment of the present application adds a fluorine-containing compound as an electrolyte additive. The fluorine element contained in the fluorine-containing compound will reduce the energy level of the lowest occupied molecular orbital (LUMO) of the molecule, so that the fluorine-containing compound will have a reduction reaction at the negative electrode interface before other solvents and additives, establish a stable SEI film, inhibit the electrochemical decomposition of DMC and chain ester solvents with similar structures, and inhibit the generation of catalysts that degrade the positive electrode tailing tape, so that the positive electrode tailing tape exhibits good electrolyte resistance, ensuring that the positive electrode tailing tape does not wrinkle during (after) high-temperature storage, and maintaining a good appearance of the battery. However, the introduction of fluorine will reduce the ionic conductivity of the electrolyte. Based on this, the embodiment of the present application adds a boron-containing compound as an electrolyte additive to ensure that there is a large amount of free Li+ in the electrolyte. Therefore, the synergistic effect of the boron-containing compound and the fluorine-containing compound can make the electrolyte and the negative electrode interface have good stability, while inhibiting the side reaction of the chain ester solvent and the catalytic degradation of the positive electrode tailing tape by the side reaction products.
[0050] Based on the above analysis, the degradation of the positive electrode finishing tape during (after) high-temperature storage is related to whether the chain ester solvent produces by-products, and whether the chain ester solvent produces by-products is related to the stability of the SEI film and the trace moisture content in the electrolyte. Further, the stability of the SEI film is related to the content of fluorine-containing compounds and boron-containing compounds, and the trace moisture content in the electrolyte is related to the total moisture content of the diaphragm and the negative electrode sheet in the battery cell before injection (since the positive electrode sheet uses an organic solvent, the water content can be ignored, and the water solvent used in the negative electrode sheet and the diaphragm mainly determines the water content in the battery cell before injection. Therefore, the water content of the battery cell before injection is mainly related to the total moisture content of the diaphragm and the negative electrode sheet). Therefore, controlling the content of fluorine-containing compounds and boron-containing compounds can maintain the stability of the SEI film; and controlling the total moisture content of the diaphragm and the negative electrode sheet in the battery cell before injection can reduce the trace moisture in the electrolyte. The content of fluorine-containing compounds and boron-containing compounds needs to be compatible with the content of chain ester solvents and the pasting area of the positive electrode tailing tape. This is because when the content of chain ester solvents is high and the content of fluorine-containing compounds and boron-containing compounds is relatively low, it will not be able to effectively improve the stability of the SEI film, causing the chain ester solvent to undergo an electrochemical reaction at the negative electrode to generate lithium methanol; when the content of chain ester solvents is low and the content of fluorine-containing compounds and boron-containing compounds is relatively high, it will cause the electrolyte viscosity to increase, the film formation impedance to increase, the lithium ion conduction efficiency to decrease, and the battery's kinetic performance to deteriorate. In addition, when the pasting area of the positive electrode tailing tape is large and the content of fluorine-containing compounds and boron-containing compounds is relatively low, the battery capacity will decrease; when the pasting area of the positive electrode tailing tape is small and the content of fluorine-containing compounds and boron-containing compounds is relatively high, the electrolyte viscosity will increase, and the positive electrode tailing tape will not be effectively prevented from wrinkling. Therefore, the inventors have found that when the organic solvent, electrolyte additive and positive electrode finishing tape satisfy 1≤A / (C+D)×B+100 / E≤4, the compatibility of the content of fluorine-containing compounds and boron-containing compounds with the content of chain ester solvents and the compatibility of the content of fluorine-containing compounds and boron-containing compounds with the bonding area of the positive electrode finishing tape can be balanced, and the trace moisture in the electrolyte can be controlled, thereby effectively inhibiting the failure of the positive electrode finishing tape during (after) high-temperature storage, and ensuring that the electrolyte has a high ionic conductivity.
[0051] As an optional embodiment, the fluorine-containing compound includes at least one of the following compounds:
[0052]
[0053]
[0054] In the embodiments of the present application, compounds 1-1 to 1-7 are fluorinated cyclic carbonate compounds, compounds 1-8 to 1-10 are fluorinated sultone compounds, and compounds 1-12 to 1-14 are fluorinated linear carbonate compounds. These compounds can undergo reduction reaction at the negative electrode interface in preference to other solvents and additives to establish a stable SEI film, which can inhibit lithium precipitation at the negative electrode, as well as inhibit the electrochemical decomposition of DMC and chain ester solvents with similar structures, inhibit the production of catalysts that degrade the positive electrode finishing tape, so that the positive electrode finishing tape exhibits good electrolyte resistance, ensures that the positive electrode finishing tape does not wrinkle during (after) high-temperature storage, and maintains a good appearance of the battery.
[0055] As an optional embodiment, the structural formula of the boron-containing compound is as follows:
[0056]
[0057]
[0058] In structural formula 2, R1, R2 and R3 are each independently selected from at least one of a H atom, a C1-C10 alkyl group, a C6-C20 aryl group and a cyano group.
[0059] Preferably, the boron-containing compound comprises at least one of the following compounds:
[0060]
[0061] In the examples of the present application, compounds 2-1 to 2-6 belong to borate compounds, which are beneficial for consuming HF generated by decomposition of the electrolyte and forming a SEI protective layer of compounds containing a BOF structure on the surface of the negative electrode. In addition, borate compounds can also form a uniform and thin CEI layer on the positive electrode side, which can further effectively reduce the dissolution of transition metal ions.
[0062] As an optional embodiment, the chain ester solvent includes at least one of diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), ethyl propionate (EP), propyl propionate (PP), methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate (MP), methyl butyrate, ethyl butyrate, methyl acrylate, and ethyl acrylate.
[0063] Preferably, the chain ester solvent includes at least propyl propionate. That is, the chain ester solvent only includes propyl propionate, or includes propyl propionate and other chain ester solvents listed above. Propionate has good compatibility with the negative electrode and is not easily oxidized and decomposed, so it is not easy to produce a catalyst that degrades the positive electrode tail tape.
[0064] As an optional embodiment, the organic solvent further includes a cyclic ester solvent, and the cyclic ester solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), γ-butyrolactone, and sulfolane.
[0065] As an optional embodiment, the mass percentage of the organic solvent in the electrolyte is 20% to 80%.
[0066] In the embodiments of the present application, the mass percentage of the organic solvent in the electrolyte may be 20%, 40%, 60%, 80% or any value within the above range, and the present application does not impose any limitation on this.
[0067] Preferably, the mass percentage of the chain ester solvent to the organic solvent is 20% to 80%.
[0068] In the embodiments of the present application, the mass percentage of the chain ester solvent to the organic solvent may be 20%, 40%, 60%, 70%, 80% or any value within the above range, and the present application does not impose any limitation on this.
[0069] As an optional embodiment, A is 20-80.
[0070] In the embodiment of the present application, the mass percentage of the chain ester solvent to the organic solvent is A%, and A can be 20%, 40%, 60%, 70%, 80% or any value within the above range, which is not limited in the present application.
[0071] Preferably, the chain ester solvent includes at least propyl propionate. In the embodiment of the present application, by controlling the chain ester solvent to include propyl propionate and the content thereof to be within the above range, the solvent can be kept stable and not prone to gas generation after high temperature storage.
[0072] As a preferred embodiment, A is 60-80.
[0073] Preferably, when propyl propionate is selected as the chain ester solvent, the mass percentage of propyl propionate in the organic solvent is 60% to 80%.
[0074] As an optional embodiment, B is 0.02-0.5.
[0075] In the embodiment of the present application, the width of the positive electrode tail tape is generally 5mm to 25mm, and the length of the positive electrode tail tape is equivalent to the length of the positive electrode sheet. The length of the positive electrode sheet of different battery cell models is different, generally 40mm to 200mm. According to experience, the area of the positive electrode tail tape is generally: 0.02dm 2 ~-0.5dm 2 The positive electrode finishing tape area within this range can be applied to most types of battery cells.
[0076] When using the positive electrode tail tape, the larger the pasting area, the better. If the pasting area is too large, the battery capacity will be reduced; if the pasting area is too small, the positive electrode tail tape will not work. Therefore, the present embodiment controls the pasting area within the above range to fully play the role of the positive electrode tail tape.
[0077] As an optional embodiment, C is 1-25.
[0078] In the embodiment of the present application, the mass percentage of the fluorine-containing compound in the electrolyte is C%, and C can be 1, 5, 10, 15, 20, 25 or any value within the above range, which is not limited in the present application. If the content of the fluorine-containing compound is too high, it will increase the viscosity of the electrolyte, reduce the conductivity of lithium ions, deteriorate the dynamics, or easily produce gas, affecting the cycle and safety performance of the battery; if the content of the fluorine-containing compound is too low, it will lead to the inability to form a stable SEI film. Therefore, the embodiment of the present application controls the content of the fluorine-containing compound within the above range, which can effectively play the role of the fluorine-containing compound.
[0079] As a preferred embodiment, C is 5-25.
[0080] In the embodiments of the present application, C can be 5, 10, 15, 20, 25 or any value within the above range, and the present application does not limit this. When C is within the above-defined range, the high temperature cycle performance of the battery can be further improved.
[0081] As an optional embodiment, D is 0.1-5.
[0082] In the embodiment of the present application, the mass percentage of the boron-containing compound in the electrolyte is D%, and D can be 0.1, 1, 3, 5 or any value within the above range, which is not limited in the present application. If the content of the boron-containing compound is too large, the impedance of the film formation will be too large, affecting the dynamic performance of the battery; if the content of the boron-containing compound is too low, it will not promote the dissociation of the lithium salt and reduce the conduction rate of the lithium ions. Therefore, the embodiment of the present application controls the content of the boron-containing compound within the above range, which can effectively play the role of the fluorine-containing compound.
[0083] As a preferred embodiment, D is 0.1-3.
[0084] In the embodiments of the present application, D can be 0.1, 1, 3 or any value within the above range, and the present application does not limit this. When D is within the above-defined range, a synergistic effect can be further exerted to improve the high temperature cycle performance of the battery.
[0085] As an optional embodiment, E<120.
[0086] In the embodiment of the present application, before injecting the electrolyte, the total moisture content of the separator and the negative electrode sheet in the battery cell is Eppm, and E can be 110, 100, 90, etc., as long as E<120 is satisfied, and the present application does not impose any limitation on this.
[0087] As an optional embodiment, A is 20-80, B is 0.02-0.5, C is 1-25, D is 0.1-5, and E<120.
[0088] Since lithium hexafluorophosphate in the electrolyte is very easy to hydrolyze, the electrolyte needs to be baked before being injected into the dry cell to control the water content in the dry cell. The total water content of the separator and the negative electrode can be tested to measure whether the dry cell meets the injection conditions. When E<120, the injection conditions are met.
[0089] As a preferred embodiment, A is 60-80, B is 0.02-0.5, C is 5-25, D is 0.1-3, and E<120.
[0090] As an alternative embodiment, see Figure 1 As shown, one end of the positive electrode tailing tape 12 is pasted in the filling area T, and the other end is pasted in the blank area K, and the area S of the positive electrode tailing tape 12 pasted in the blank area K is K Larger than the area S pasted in the filler area T T .
[0091] In the embodiment of the present application, the area S of the positive electrode tailing tape 12 pasted in the blank area K is controlled. K Larger than the area S pasted in the filler area T T It can not affect the embedding of lithium ions in the positive electrode active material in the filling area, and prevent lithium precipitation at the corresponding position of the junction between the tail filling area and the blank area, and at the same time will not affect the capacity of the battery.
[0092] As a preferred embodiment, see Figure 1 As shown, the area of the positive electrode tailing tape pasted in the blank area is S K The area of the positive electrode tail tape pasted in the filler area is S T , 1.5S T ≤S K ≤2S T .
[0093] The area of positive electrode tail tape pasted in the blank area is not as large as possible, and the area pasted in the filling area is not as small as possible. When the 1.5S T ≤S K ≤2S T When used in this way, there can be sufficient safety margin without affecting the battery capacity.
[0094] In the embodiment of the present application, the lithium salt includes one or more of lithium hexafluorophosphate LiPF6, lithium difluorooxalatoborate LiODFB, lithium difluorobis(oxalatophosphate LiDFOP, lithium tetrafluoroborate LiBF), lithium bis(trifluoromethylsulfonyl)imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, and lithium difluorophosphate LiPOF2, and the lithium salt accounts for 10% to 30% of the mass percentage of the electrolyte.
[0095] In an embodiment of the present application, the electrolyte additive also includes other additives, including but not limited to vinylene carbonate VC, 1,3-propane sultone PS, vinyl sulfate DTD, succinonitrile SN, adiponitrile ADN, 1,3,6-hexanetrinitrile HTCN, propylene sultone PST, methylene disulfonate MMDS, ethylene glycol bis(propionitrile) ether EGBE, pentafluoroethoxyphosphazene, dicyclohexylcarbonyl, trimethyl imide phosphate, hexamethylene diisocyanate, etc.
[0096] In the embodiment of the present application, the electrolyte additive accounts for 5% to 35% of the mass percentage of the electrolyte.
[0097] An embodiment of the present application also provides an electronic device, comprising the aforementioned electrochemical device.
[0098] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0099] In order to further understand the present invention, the present application is described below in conjunction with embodiments. These embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0100] 1. Preparation of batteries
[0101] (1) Preparation of electrolyte
[0102] A chain ester solvent and a cyclic ester solvent were mixed according to the mass ratio in Table 1 to serve as an organic solvent, wherein the mass percentage of the organic solvent in the electrolyte was 75%, and the mass percentage of the chain ester solvent in the organic solvent was set according to Table 1. LiPF6 was then added to obtain a mixed solution with a LiPF6 concentration of 1.1 mol / L, and the first additive and the second additive, as well as 4% of succinonitrile SN and 4% of 1,3-propane sultone PS were added to the mixed solution according to Table 1 to prepare electrolytes of various embodiments and comparative examples.
[0103] (2) Production of positive electrode:
[0104] The lithium nickel manganese cobalt ternary positive electrode active material, the conductive agent CNT, and the binder polyvinylidene fluoride are fully stirred and mixed in N-methylpyrrolidone solvent at a weight ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The slurry is applied to the a surface of the positive electrode collector aluminum foil and the filler area of the b surface of the positive electrode collector aluminum foil, and then the positive electrode tailing tape is pasted between the filler area and the blank area of the b surface. The pasting area of the positive electrode tailing tape is set according to Table 1; after drying and cold pressing, the positive electrode sheets of each embodiment and comparative example are obtained.
[0105] (3) Production of negative electrode sheet:
[0106] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector Cu foil, dried, and cold pressed to obtain a negative electrode sheet.
[0107] (4) Production of lithium-ion batteries:
[0108] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, so that the separator is in the middle of the positive and negative electrodes to play an isolating role, and then wound to a bare cell. The bare cell is placed in a shell, and the cell is baked at 80°C. The total moisture content of the separator and the negative electrode sheet in the cell is controlled according to Table 1, and the electrolytes of each embodiment and comparative example are respectively injected into the dried cell, and the preparation of the lithium-ion battery is completed after vacuum packaging, standing, forming, shaping and other processes.
[0109] Table 1 Recipe and relationship table
[0110]
[0111]
[0112]
[0113]
[0114]
[0115] 2. Performance Test
[0116] 1. Lithium deposition at the negative electrode at 0℃: discharge at 0.2C to 3V at 25℃, then stand at 0℃ for 3H, charge to 4.53V at 0.34C constant current and constant voltage, cut-off current 0.05C, then discharge to 2.8V at 0.5C, repeat the cycle for 50cls, disassemble the fully charged battery, and observe the lithium deposition state at the negative electrode interface.
[0117] 2. Performance of 28D storage at 60℃: The battery is charged to 4.53V at 0.5C constant current, with a cut-off current of 0.05C, and left to stand for 10 minutes. The fully charged thickness D0 is tested. The battery is left to stand at 60±2℃ for 28D with full charge in an open circuit. The hot thickness D1 is tested immediately after it is taken out of the box. Thickness change rate = D1 / D0-1.
[0118] 3. 60℃ storage 28D appearance test: observe whether the battery produces gas and whether the positive electrode tail tape (referred to as tape) is corrugated.
[0119] The above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 2.
[0120] Table 2 Test results
[0121]
[0122]
[0123] Combining the data in Table 1 and Table 2, by comparing Examples 1 to 14, and Examples 17 to 21, it can be seen that by using the fluorine-containing compounds and boron-containing compounds provided in the embodiments of the present application, and satisfying 1≤A / (C+D)×B+100 / E≤4, the failure of the positive electrode finishing tape during (after) high-temperature storage can be effectively suppressed, and the electrolyte can be ensured to have a high ionic conductivity.
[0124] By comparing Example 14 and Example 40, it can be seen that replacing PP with EP will cause battery gas production, affecting the safety performance of the battery; by comparing Example 14 and Example 41, it can be seen that using EP+PP has a synergistic effect and can improve the safety performance of the battery; by comparing Example 14 and Example 42, replacing PP with DMC will cause battery gas production, affecting the safety performance of the battery; by comparing Example 41 and Example 43, DMC+PP also has a synergistic effect and can improve the safety performance of the battery; further combined with Example 44, it can be seen that the synergistic effect of DMC+EP is not as good as EP+PP and DMC+PP, therefore, the chain ester solvent obtained in the examples of the present application preferably contains at least PP.
[0125] By comparing the various embodiments and comparative examples, and combining Example 39 and Comparative Example 14, it can be seen that when 1≤A / (C+D)×B+100 / E≤4 is satisfied, the failure of the positive electrode finishing tape during (after) high-temperature storage can be effectively suppressed, and the electrolyte can be ensured to have a high ionic conductivity.
[0126] Although the present application has been described with reference to preferred embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from the scope of the present application. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the present application without departing from the substantive scope of the present application. Therefore, the present application is not intended to be limited to the specific embodiments disclosed as the best mode of implementing the present application contemplated, but the present application will include all embodiments falling within the scope of the appended claims.
[0127] All ranges disclosed in this application are inclusive of the endpoints, and the endpoints are combinable with each other.
[0128] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrochemical device, characterized in that The invention comprises a shell, a battery cell arranged in the shell, and an electrolyte injected into the shell, wherein the electrolyte comprises a lithium salt, an organic solvent and an electrolyte additive, wherein the organic solvent comprises a chain ester solvent, and the electrolyte additive comprises a fluorine-containing compound and a boron-containing compound; the battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises a positive electrode current collector, wherein one side surface of the positive electrode current collector comprises a blank area and a filler area, wherein the filler area is coated with a positive electrode active material layer, and a positive electrode tailing tape is pasted between the blank area and the filler area, and the positive electrode tailing tape faces the separator; The organic solvent, the electrolyte additive and the positive electrode finishing tape satisfy the following relationship: 1≤A / (C+D)×B+100 / E≤4 In the formula, the mass percentage of the chain ester solvent to the organic solvent is A%, and the pasting area of the positive electrode tailing tape is B dm 2 , C is the mass percentage of the fluorine-containing compound in the electrolyte is C%, the mass percentage of the boron-containing compound in the electrolyte is D%, and before injecting the electrolyte, the total moisture content of the separator and the negative electrode sheet in the battery cell is E ppm.
2. The electrochemical device according to claim 1, characterized in that The fluorine-containing compound comprises at least one of the following compounds:
3. The electrochemical device according to claim 1, characterized in that The structural formula of the boron-containing compound is as follows: In structural formula 2, R1, R2 and R3 are each independently selected from at least one of a H atom, a C1-C10 alkyl group, a C6-C20 aryl group and a cyano group.
4. The electrochemical device according to claim 3, characterized in that The boron-containing compound comprises at least one of the following compounds:
5. The electrochemical device according to claim 1, characterized in that The chain ester solvent includes at least one of diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, ethyl propionate, propyl propionate, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate, methyl butyrate, ethyl butyrate, methyl acrylate, and ethyl acrylate; preferably, the chain ester solvent contains at least propyl propionate; and / or, the organic solvent further includes a cyclic ester solvent, and the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, and cyclopentane sulfone.
6. The electrochemical device according to claim 1, characterized in that The mass percentage of the organic solvent in the electrolyte is 20% to 80%.
7. The electrochemical device according to any one of claims 1 to 6, characterized in that: A is 20-80; and / or, B is 0.02-0.5; and / or, C is 1-25; and / or, D is 0.1-5; and / or, E<120.
8. The electrochemical device according to claim 7, characterized in that A is 40 to 80; C is 5 to 25; and / or D is 0.1 to 3.
9. The electrochemical device according to claim 1, characterized in that One end of the positive electrode tailing tape is pasted in the filler area, and the other end is pasted in the blank area, and the area S of the positive electrode tailing tape pasted in the blank area is K Greater than the area S pasted in the filler area T ; Preferably, 1.5S T ≤S K ≤2S T .
10. An electronic device, characterized in that: Comprising the electrochemical device according to any one of claims 1 to 9.
Citation Information
Patent Citations
Electrochemical device and electronic device
CN113964375A
Battery
CN114050232A
Battery
CN114094049A
Nonaqueous electrolytic solution, and lithium ion secondary battery
JP2013125625A
Nonaqueous electrolyte battery
US20140272552A1